Integrity of API 5L X56 Offshore Pipeline Subjected to Girth Weld Anomalies and Corrosion Using Probabilistic Methods - Salina Farini Bahaman, U. (American Society of Civil Engineers (ASCE), 2022)
Imperfections or uneven surfaces of welded areas due to uncertain errors such as equipment, weld quality, or mechanical damage may cause defects or anomalies such as corrosion or cracks and lead to other failures such as burst or leakage. Corrosion tends to occur at the uneven area due to the stagnation of the hydrocarbons for a long period, which directly can reduce the strength of the pipeline itself. This paper proposes a framework that incorporates structural reliability analysis (SRA) to analyze the safety and integrity levels of corroded girth welded API 5L X56 pipeline. By developing the limit state functions (LSFs) with reference to previous studies and existing codes and standards, the assessment was divided into two sections: assessing the pipeline as a single pipeline, and as sectional parts (girth welded area) of the pipeline. The probabilistic evaluation was carried out using Monte Carlo simulation (MCS), and the obtained results were compared in terms of the failure probability, Pf. The results demonstrated that two burst pressure models - the Shell-92 and Zhang et al. models - are highly conservative based on the failure probability, whereas the pipeline corrosion failure criterion (PCORRC) gives the most reasonable results for both general corroded and girth welded pipeline scenarios. The findings of this work also indicate that the failure probability in sectional pipes is more reliable than that in entire pipes due to the consideration of corrosion distributions in the pipeline. Â© 2022 American Society of Civil Engineers.